Retinal Angiomatous Proliferation and Intravitreal Bevacizumab Injection - Kang, Jae Hoon (The Korean Ophthalmological Society, 2007)
PURPOSE: To evaluate the short-term efficacy and safety of intravitreal bevacizumab injection (IVBI) in patients with retinal angiomatous proliferation (RAP). METHODS: Seven eyes of 5 patients with RAP were included in this study. All of the eyes evidenced stage 2 RAP lesions, except for one eye with a stage 3 lesion. IVBI (1.25 mg/0.05 cc) were conducted at 4 or 6-week intervals. Complete ocular examinations, angiographic results and optical coherence tomographic findings before and after the IVBI were analyzed at baseline and upon the follow-up visits. RESULTS: Seven eyes were studied in 5 patients who had undergone IVBI. Partial (3 eyes) or complete (4 eyes) regression of RAP was noted after IVBI in all of the studied eyes. Visual acuity improved in 5 of the eyes, and was stable in 2 of the eyes. One eye evidenced severe intraocular inflammation after IVBI and a subsequent development of new RAP, which was controlled with vitrectomy and repeat IVBI. CONCLUSIONS: This treatment was effective over 6 months, stabilizing or improving visual acuity and reducing angiographic leakage. These short-term results suggest that IVBI may constitute a promising therapeutic option, particularly in the early stages of RAP.